Penyelesaian Sengketa Perusakan Lingkungan Hidup pada Hutan Adat Masyarakat Sabuai - Harudin, Harlinud; Angga, La Ode; Latupono, Barzah (BAMETI Customary Law Review, 2023)
The geographical location of the Sabuai settlement has been crossed by five rivers, but when the forest upstream of the river is destroyed, the settlement will automatically have a bad impact. The destruction of the Sabuai tribal forest not only caused flooding in settlements, but also resulted in damaged residents' gardens, and crop failures, and even clean water sources were also buried by landslides. The efforts of indigenous peoples to fight for and defend their environment are very difficult. This can be seen from Sabuai Country, Pamatang Siwalalat District, Eastern Seram Regency. The indigenous people of Sabuai struggle to defend their customary forests and are in conflict with CV. Source of Prosperous Blessings. The type of research conducted in this writing is normative juridical law research that is descriptive and analytical. Normative legal research is a form of legal writing that is based on the characteristics of normative law. The results obtained in this study are: There are two (2) paths of environmental dispute resolution, namely out-of-court (non-litigation) or out-of-court settlement also called Alternative Dispute Resolution (ADR), in its implementation Alternative Dispute Resolution consists of negotiation, mediation, conciliation and arbitration and case resolution can be carried out by litigation or non-litigation routes. The settlement of cases by the litigation route means that the settlement of legal issues is carried out in court, The form of legal responsibility in this writing is a form of absolute responsibility (without error). The term unlawful act (onrechtmatig daad) before 1919 by the Hoge Raad was interpreted narrowly, that is, any act that is contrary to the rights of another person arising from the law or any act that is contrary to his own legal obligations arising from the law.